2017
DOI: 10.1177/0194599817699596
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Cadaver Model for the Instruction of Ultrasound‐Guided Fine‐Needle Aspiration of Thyroid Nodules

Abstract: Objective The aim of our study is to determine if a fresh cadaver model (FCM) for the instruction of ultrasound (US)-guided fine-needle aspiration (FNA) of thyroid nodules is a practical method for instruction. Study Design Pre- and postinstruction assessment of medical students' ability to perform US-guided FNA of artificially created thyroid nodules placed adjacent to the thyroid gland of a fresh cadaver. Setting University-based fresh cadaver laboratory. Subjects and Methods Study participants included a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For example, a pilot study by a group from the University of Arizona showed that medical students could successfully learn FNA techniques by practicing on the thyroids of cadavers. 6 In another study, Schnadig et al performed cytologic diagnosis of lesions seen at autopsy, using both scrapings and benchtop FNAs. 7 This study was a continuation of the work done by Walker and Going.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a pilot study by a group from the University of Arizona showed that medical students could successfully learn FNA techniques by practicing on the thyroids of cadavers. 6 In another study, Schnadig et al performed cytologic diagnosis of lesions seen at autopsy, using both scrapings and benchtop FNAs. 7 This study was a continuation of the work done by Walker and Going.…”
Section: Discussionmentioning
confidence: 99%
“…There is some literature on benchtop FNA, with studies spanning a range of applications. For example, a pilot study by a group from the University of Arizona showed that medical students could successfully learn FNA techniques by practicing on the thyroids of cadavers 6 . In another study, Schnadig et al performed cytologic diagnosis of lesions seen at autopsy, using both scrapings and benchtop FNAs 7 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Practicing on artificial models adjacent to a cadaver's thyroid or breast, medical students demonstrated improvements in technical skills related to ultrasound-guided FNA, as assessed with checklists. 2,3 Similar checklists can easily be used for instructing pathology residents and cytopathology fellows in smear preparation and FNA techniques. This type of approach, evaluating the performance of discrete tasks, will likely propagate as we move toward adopting entrustable professional activities.…”
Section: On-site Evaluation and Fine-needle Aspiration (Fna) Checklistsmentioning
confidence: 99%
“…A checklist has been used to assess FNA performance in surgery residents, and a short instructional video was associated with improved scores . Practicing on artificial models adjacent to a cadaver's thyroid or breast, medical students demonstrated improvements in technical skills related to ultrasound‐guided FNA, as assessed with checklists . Similar checklists can easily be used for instructing pathology residents and cytopathology fellows in smear preparation and FNA techniques.…”
Section: On‐site Evaluation and Fine‐needle Aspiration (Fna) Checklistsmentioning
confidence: 99%